The Nutritional Status of Grade Eleven Students in the Medical Officer of Health Area Kalutara - S De Silva (Journal of the College of Community Physicians, 2011)
Objectives: To describe the nutritional status of grade eleven school children in the Medical Officer of Health (MOH) area Kalutara. Methodology: A descriptive cross-sectional study was carried out among grade eleven school children in Type 1AB and Type 1C state schools in the MOH area Kalutara. Eighteen classes from a total of 14 schools were studied. Cluster sampling technique, probability proportionate to size was used to select the sample. The heights and weights were measured, and the Body Mass Index (BMI) was calculated for each child. The age and sex specific BMI charts developed by the National Centre for Health Statistics 2000 were used as standards. A structured, pre-tested self-administered questionnaire was used to collect the socio-demographic characteristics. Results : The prevalence of thinness (<5th percentile) was 35.4% and the prevalence of being at risk of overweight (≥85th percentile) was 6.7%. Conclusions: Under-nutrition is a problem among grade eleven school children in the MOH area Kalutara. Almost 7% of them were at risk of overweight. Key Words: Nutritional Status; School Children DOI: 10.4038/jccpsl.v13i2.2967 Journal of the College of Community Physicians of Sri Lanka Vol.13(2) 2008 34-38